Democratic Leadership Style of The Village Head of Bontomarannu, South Galesong District, Takalar Regency - Saharuddin, Reski Army; Madani, Muhlis; Riskasari (Golden Ratio of Data in Summary, 2025)
This study aims to determine which leadership style is owned by the village head according to the indicators of the leadership style to give an overview. The type of research used is qualitative. The data sources used are primary and secondary. The number of informants is 8. Data collection was carried out using observation techniques, interviews, and documentation. Data analysis techniques using data reduction steps, data presentation, data verification, and using triangulation data validation, namely, triangulation of sources, techniques, and time. The results of this study indicate that the leadership style of the village head Bontomarannu must have a village head must have a leadership style good in decision-making, motivating, communication, controlling subordinates, and taking responsibility. Head of Bontomarannu Village demonstrates a participative and inclusive attitude, has good skills in decision-making, motivating and communicating skills with the community and village apparatus, and can control their subordinates with various approaches. However, there is still a lack of responsibility in managing development projects and caring for community organizations such as Karang Taruna.